If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -11 + 4x = 2 + (2x + 1) Reorder the terms: -11 + 6x + 4x = 2 + (2x + 1) Combine like terms: 6x + 4x = 10x -11 + 10x = 2 + (2x + 1) Reorder the terms: -11 + 10x = 2 + (1 + 2x) Remove parenthesis around (1 + 2x) -11 + 10x = 2 + 1 + 2x Combine like terms: 2 + 1 = 3 -11 + 10x = 3 + 2x Solving -11 + 10x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -11 + 10x + -2x = 3 + 2x + -2x Combine like terms: 10x + -2x = 8x -11 + 8x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 -11 + 8x = 3 + 0 -11 + 8x = 3 Add '11' to each side of the equation. -11 + 11 + 8x = 3 + 11 Combine like terms: -11 + 11 = 0 0 + 8x = 3 + 11 8x = 3 + 11 Combine like terms: 3 + 11 = 14 8x = 14 Divide each side by '8'. x = 1.75 Simplifying x = 1.75
| 14a+b=73 | | 5x-4=6x+2 | | 3a/11-1=7a/11+9 | | (X^2+X-3)*3=(2X-8)*(2X+5) | | 8x-4=5x-2 | | 7a-3b=26 | | -3b=9 | | 3-x=9+6x | | 7[6-(-6x-3)]=84x+84 | | (2.5)x+(0.25)x=(2.75)+x | | 7x+4=-2x+4+9x | | 4x-5y=-13 | | 6-5x=2-3x | | 3x^2-9x+3x^2=0 | | 2x-7y=-29 | | 7x=9-3 | | 15x-8y=0 | | (11x^2+4)-(9x^2-9)=0 | | 9x-14-2x=9x+2-5x | | 6x+2=2+6x | | 8y^2-34y-30=0 | | [8-8(1-9)]= | | 5x^2+3x^2+2=0 | | 4(-x+1)-(5-3x)=1 | | 5x^3+4x^2+7x+8=0 | | 21-(7x-4)=6x-3 | | 6a+3b-2(8a-3b)= | | -3ab^2+6ab-3= | | 4x^2-29x+49=0 | | 8x-21+5x=-15 | | -(5x-8y-49)= | | (-64)*(+4)= |